Uterus preserving surgery versus hysterectomy in the treatment of refractory postpartum haemorrhage in two tertiary maternity units in Cameroon: a cohort analysis of perioperative outcomes - Julius Sama Dohbit; Pascal Foumane; Elie Nkwabong; Christelle Ogolong Kamouko; Joel Noutakdie Tochie; Bernard Otabela; Emile Mboudou (BMC, 2017)
Abstract Background Little evidence exists on the efficacy and safety of the different surgical techniques used in the treatment of postpartum haemorrhage (PPH). We aimed to compare uterus preserving surgery (UPS) versus hysterectomy for refractory PPH in terms of perioperative outcomes in a sub-Saharan African country with a known high maternal mortality ratio due to PPH. Methods This was a retrospective cohort study comparing the perioperative outcomes of all women managed by UPS (defined as surgical interventions geared at achieving haemostasis while conserving the uterus) versus hysterectomy (defined as surgical resection of the uterus to achieve haemostasis) for PPH refractory to standard medical management in two tertiary hospitals in Cameroon from January 2004 to December 2014. We excluded patients who underwent hysterectomy after failure of UPS. Comparison was done using the Chi-square test or Fisher exact test where appropriate. Bonferroni adjustment of the p-value was performed in order to reduce the chance of obtaining false-positive results. Results We included 24 cases of UPS against 36 cases of hysterectomy. The indications of surgery were dominated by uterine rupture and uterine atony in both groups. Types of UPS performed were seven bilateral hypogastric artery ligations, seven hysterorraphies, six bilateral uterine artery ligations, three B-Lynch sutures and one Tsirulnikov triple ligation with an overall uterine salvage rate of 83.3%. Types of hysterectomies were 26 subtotal hysterectomies and 10 total hysterectomies. UPS was associated with maternal deaths (RR: 2.3; 95% CI: 1.38-3.93.; p: 0.0015) and postoperative infections (RR: 1.96; 95% CI: 1.1-3.49; p: 0.0215). The association of UPS with maternal death was not attenuated after Bonferroni correction. Hysterectomy had no statistically significant adverse outcome. Conclusion Hysterectomy is safer than UPS in the management of intractable PPH in our setting. The choice of UPS as first-line surgical management of PPH in resource-limited settings should entail diligent anticipation of these adverse maternal outcomes in order to lessen the perioperative burden of PPH.